Projects in Automatic Control 2023 - Johnsson,Charlotta (2023)
The Department of Automatic Control at Lund University bi-annually gives a project course in Systems, Control and Learning (FRTN70). The course is given at the advanced level (7.5 ECTS credits), and the studentswork in small teams to achieve a common goal. The projects typically involve a real-world estimation or control problem with relevance to industrial or other applications. In this course, the students get an opportunity to explore implementational aspects of concepts they have learned in previous control systems courses.With a faculty member or doctoral student as an advisor, the groups independently formulate an objective and an associate time plan. Subsequent activities typically involve modelling, controller design, implementation, documentation, and verification. The students present their work through two feedback seminars, an oral presentation, a demonstration session, and a written report. The reports of the fall 2023 edition of the course are presented in this booklet. This year, the cohort consisted of 28 students, working in teams of 4-5 persons. The course included 6 projects; Impedance control ,Planar pushing with visual feedback, Self-balancing cube, Self-balancing bicycle using reaction wheels, Omibot tag, and Omnibot asteroids. Every group managed to perform successful and satisfactory real-time experiments to generate the final experimental results ready in time for the demonstration in January 2024. Doctoral students Felix Agner, Marko Guberina, and Olle Kjellqvist have served the course as project advisors, research engineers Alexander Pisarevsky, Anders Blomdell and Anders Nilsson have supported the groups throughout their projects, and Mika Nishimura has help with student registration and related matters. To find out more about the course, please visit http://www.control.lth.se/course/FRTN70. Lund, February 2024 Charlotta Johnsson, Course responsible FRTN70